PELATIHAN DI SMA DAERAH JAKARTA PUSAT BUKU BESAR DAN NERACA SALDO PADA PERUSAHAAN JASA - Viriany; Wieleycia Terence; Erica; Melvin Vanwi Goenawan (Jurnal Serina Abdimas, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) program is a policy issued by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. One of the MBKM activities being undertaken is teaching assistance outside the campus. This program provides an opportunity for students to gain teaching experience, one of which is by teaching at the Senior High School level. This assistance program is conducted at SMA Tarsisius 1, teaching extracurricular activities for grades X, XI, and XII, focusing on material related to the general ledger and trial balance. The selection of SMA Tarsisius 1 as a partner was made because students still have limited understanding of the general ledger and trial balance. This is due to their difficulty in distinguishing the function of each account and making mistakes in classifying accounts as debit or credit. To address this issue, the team will focus on delivering structured material that aligns with the accounting cycle. The lessons will also be connected to real-life transactions to help students better understand the material. After presenting the material, there will be a question-and-answer session to ensure that the students have a clear understanding of the material presented. Through this training, it is also hoped that students will gain a better understanding of the general ledger and trial balance, enabling them to apply the knowledge and skills they gain in the future. For university students, it is expected that this program will enhance their communication skills, socialization, and the ability to share knowledge on lessons learned during their studies. With this program, it is hoped that it can improve the quality of the younger generation and help them overcome global challenges. Program Merdeka Belajar Kampus Merdeka merupakan kebijakan yang dikeluarkan oleh Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi Republik Indonesia. Program MBKM yang diambil yaitu kegiatan asistensi mengajar di luar kampus. Program ini memberi kesempatan kepada mahasiswa untuk mencari pengalaman mengajar, salah satunya dengan mengajar tingkat Sekolah Menengah Atas. Program asistensi ini dilakukan di SMA Tarsisius 1 dengan mengajar kegiatan ekstrakulikuler kelas X, XI, XII dengan mengajarkan materi seputar buku besar dan neraca saldo. Pemilihan SMA Tarsisius I sebagai mitra dikarenakan siswa masih kurang paham terkait buku besar dan neraca saldo. Hal ini disebabkan karena sulit membedakan fungsi setiap akun yang ada dan terjadinya kesalahan dalam mengelompokkan akun sesuai debit atau kreditnya. Untuk mengatasi masalah, ini tim akan lebih berfokus pada penyampaian materi yang telah dibuat sebelumnya dengan terstruktur sesuai siklus akuntansi. Pembelajaran juga akan dikaitkan dengan transaksi yang terjadi sehari-hari agar siswa/i lebih memahami materi. Setelah memaparkan materi, akan ada sesi tanya jawab untuk memastikan siswa/i sudah memahami dengan baik materi yang telah disampaikan. Melalui pelatihan ini juga, diharapkan siswa/i dapat memperoleh pemahaman yang lebih baik terkait buku besar dan neraca saldo sehingga ilmu dan kemampuan yang didapat dapat dimanfaatkan ke depannya. Bagi mahasiswa, diharapkan dengan adanya program ini bisa menambah keterampilan dalam berkomunikasi , bersosialisasi dan berbagi ilmu mengenai pelajaran yang sudah dipelajari selama perkuliahan. Dengan adanya program ini, diharapkan bisa meningkatkan generasi muda yang berkualitas dan dapat mengatasi tantangan global.